Fair Tax Compliance: Tax Rate Changes, Calculation Methods, and System Modernization: Peningkatan Kepatuhan Pajak pada UKM melalui Perubahan Tarif, Metode Perhitungan, dan Modernisasi Sistem: Mengutamakan Keadilan - Rizky Ardiantari; Sriyono Sriyono (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative descriptive study aims to examine the influence of tax rate changes, calculation methods, and system modernization on tax compliance among Small and Medium-sized Enterprise (SME) taxpayers, with tax fairness as a moderating variable. The research was conducted at the South Sidoarjo Pratama Tax Office, with a sample size of 100 SME taxpayers selected using purposive sampling based on turnover and one year of tax registration. Primary data were collected through direct survey questionnaires and analyzed using multiple linear regression analysis and moderated regression analysis with an absolute difference approach. The findings reveal a positive relationship between tax rate changes, calculation methods, and system modernization, and tax compliance among SME taxpayers. These results emphasize the significance of tax fairness in promoting compliance among SMEs, thereby having important implications for tax policy and administration. The study sheds light on the factors that can enhance tax compliance and provides valuable insights for policymakers and tax administrators to foster a fair and effective tax system. Highlights: Tax fairness as a moderating variable: The study investigates the role of tax fairness in influencing tax compliance among SME taxpayers, highlighting the importance of equitable taxation policies and practices. Positive relationship between tax factors and compliance: The research findings reveal a positive association between tax rate changes, calculation methods, system modernization, and tax compliance among SMEs, emphasizing the need for effective tax policies and administration. Implications for tax policy and administration: The study provides valuable insights for policymakers and tax administrators on the significance of tax fairness in promoting compliance among SMEs, guiding the development of fair and effective tax systems to encourage voluntary tax compliance. Keywords: tax compliance, Small and Medium-sized Enterprises (SMEs), tax rate changes, calculation methods, system modernization.